Participation in the Virtual Environment of Blended College Courses: An Activity Study of Student Performance - Cavanaugh, Cathy; Hargis, Jace; Mayberry, John (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
This paper describes a study of success factors in the introductory semester of liberal studies blended courses offered at the bachelor of science level. The influence of student participation in the online course environment was examined, as measured by the number of times students logged into the learning management system (LMS) and average session length. These measures were correlated with final course grades to increase understanding of the participation patterns of successful students. The resulting patterns and their implications are identified. We observe that students with an intermediate number of logins and average session length tended to exhibit the optimal level of course performance with students who logged in near the low or high amount of times tending to receive lower grades.